Adverse events in the treatment of spinal muscular atrophy in children and adolescents with nusinersen: A systematic review and meta-analysis - Zhong, Zhi-Juan; Zheng, Pi-Mei; Dou, Hui-Hong; Wang, Ji-Gan (Frontiers in Pediatrics, 2023)
Objectives To systematically analyze adverse events (AEs) in treatment of spinal muscular atrophy (SMA) with Nusinersen in children and adolescents. Methods The study is registered on PROSPERO (CRD42022345589). Databases were searched and literature relating to Nusinersen in the treatment of spinal muscular atrophy in children from the start of database establishment to December 1, 2022, was retrospectively analyzed. R.3.6.3 statistical software was used, and random effects meta-analysis was performed to calculate weighted mean prevalence and 95% confidence intervals (CI). Results In total, 15 eligible studies were included, with a total of 967 children. Rate of definite Nusinersen-related AEs was 0.57% (95% CI: 0%–3.97%), and probable Nusinersen-related AEs 7.76% (95% CI: 1.85%–17.22%). Overall rate of AEs was 83.51% (95% CI: 73.55%–93.46%), and serious AEs 33.04% (95% CI: 18.15%–49.91%). For main specific AEs, fever was most common, 40.07% (95% CI: 25.14%–56.02%), followed by upper respiratory tract infection 39.94% (95% CI: 29.43%–50.94%), and pneumonia 26.62% (95% CI: 17.99%–36.25%). The difference in overall AE rates between the two groups (Nusinersen group and placebo group) was significant (OR = 0.27,95% CI: 0.08–0.95, P = 0.042). Moreover, incidence of serious adverse events, and fatal adverse events were both significantly lower than in the placebo group (OR = 0.47, 95%CI: 0.32–0.69, P < 0.01), and (OR = 0.37, 95%CI: 0.23–0.59, P < 0.01), respectively. Conclusion Nusinersen direct adverse events are rare, and it can effectively reduces common, serious, and fatal adverse events in children and adolescents with spinal muscular atrophy.